Estimation of adhesive joint failure initiation using FEM - Agnieszka Derewonko; Pavlo Maruschak; Paweł Prusko (Biuletyn Wojskowej Akademii Technicznej, 2024)
In adhesive joints, the integrity of the adhesive and the joined parts results from intermolecular forces. The determinationof the total elastic energy at the interface of two different bodies is possible by introducing the contact problem in the numerical modelof the system. The paper presents the optimization of a single lap adhesive joint by estimating the tensile force causing the joint failureinitiation and its location based on the calculated elastic energy. This approach limits the number of experimental tests. Limitation ofthe estimation, resulting from dimension of the applied finite element mesh, is also considered. The application is demonstrated througha numerical analysis of a quasi-static tension test on a single-lap adhesive joint without spacers. Two models, created based on the describedlimitations, are analyzed. The calculated surface energy values are presented as three-dimensional graphs in the Matlab environmentfor one of the bonding surfaces. The selection of this surface is justified by a brief theoretical analysis.